European Union policy in relation to the sector of insurance – The consequences for the Polish market - Treder, Hanna (Publishing House of the Wrocław University of Economics, 2009)
The sector of insurance as an integral part of the European financial market is an important area of European Union policy including all the member countries. This policy aims at shaping the conditions for the development of this sphere of economic activity which is the insurance. The significance of insurance is connected with its crucial functions, not only economic but also social, which are realised as insurance coverage offered on the market by insurance companies. Faced with various threats, which in the modern world result from economic and civilisation development, insurance is used not only to compensate for the negative results of acts of God but it can also be a crucial stimulus to undertake innovative economic projects or it can be used to alleviate negative results of social phenomena. Thus the aim of the policy led by the EU with reference to insurance sector has to be not only ensuring optimum conditions for the development of this market but also establishment and execution of specific safety standards for its participants. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 442-451